Chatbot, ChatGPT: artificial intelligence and/or business intelligence and/or robotic untruths, for now - Passos, Mauro Romero Leal; Júnior, José Eleutério (Brazilian Journal of Sexually Transmitted Diseases, 2023)
The authors, like most humans on the planet at all times, go through many profound transformations throughout their lives. Let’s imagine hominids starting to master fire more than a million years ago. Inventing the wheel, writing, navigating the seas, inventing the light bulb, motor vehicles, Santos Dumont’s plane, telex, teleradiography, and so many other things that for each era, it was unimaginable such an advance would be incorporated into daily of human life. Today, in 2023, we are facing a computerized conversation through the world wide web, the internet. For now, called artificial intelligence – AI, chatbot. How much will this technology add benefits in the health area? When will this technology spread untruths? How much will people blindly follow the information and experience huge gains and marked problems, side effects? In these dialogues with the various chatbots already being made available, free or with payment of monthly fees, can these computer programs, after several human-AI arguments, write that, for the situations presented in a given conversation, suicide is plausible conduct? The concerns of the authors are concerns that are valid in March 2023. The editorial tests conversations. And time will show us how to learn, teach, live together, and transform this artificial intelligence.